2014
DOI: 10.1590/s0103-90162014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Individual tree growth models for eucalyptus in northern Brazil

Abstract: The diameter and height growth model is one of three submodels used for simulating individual tree growth. In Brazil, there are few studies on the dimensional growth of individual trees be they native or exotic species, despite their potential. This study aimed to evaluate diameter and height growth models for individual trees for eucalyptus stands and to validate the best fitting model. Tree diameter and height data were obtained from 48 permanent plots of unthinned stands of Eucalyptus grandis × Eucalyptus u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 31 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…In this research, the repeatability of different traits ranged from 0.76 to 0.99, which indicated that a great deal of variation in these clones was repeatable. These results agree with Yang et al [25] for Eucalyptus and Martins et al [30] for Casuarina. High repeatability estimates indicate that the selection for these traits is effective and less influenced by environmental effects [31].…”
Section: Genetic and Variation Parameterssupporting
confidence: 92%
“…In this research, the repeatability of different traits ranged from 0.76 to 0.99, which indicated that a great deal of variation in these clones was repeatable. These results agree with Yang et al [25] for Eucalyptus and Martins et al [30] for Casuarina. High repeatability estimates indicate that the selection for these traits is effective and less influenced by environmental effects [31].…”
Section: Genetic and Variation Parameterssupporting
confidence: 92%
“…The data from each plot at 72 months were used to project the DBH and Ht up to 120 months, at 12month intervals. For that, a complete model at the individual tree level was used in a projection structure of the variables, at a current age for a future age (t → t + 1), adjusted for the study area by Martins et al (2014). The equations were developed for each productive capacity classes: S32 where: I1 and I2 are the current (1) and future (2) ages (months); DBH1 and DBH 2 are the diameters at breast height in the current (1) and future (2) ages (cm); Ht1 and Ht2 are the total heights in the current (1) and future (2) ages (m); S is the location index.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis and modeling of dendroecological data by growth functions can provide information on growth patterns to predict feasible target diameters and to evaluate and adjust current forest management practices. However, the models constructed by traditional linear or nonlinear growth functions are difficult to apply to sites with complex conditions due to the inability to account for the influence of stochastic factors such as site factors [20,21]. The mixed-effects models can effectively solve this problem.…”
Section: Introductionmentioning
confidence: 99%